Performance of laminated oil palm veneer lumber (LOPVL) bonded using UF, MUF and PF adhesives / Zulhazmi Ahmed - Ahmed, Zulhazmi (2009)
Oil palm trunk (OPT) has the potential to be converted into lumber, panels and composites products. However, the result on some of the attempted product was not satisfying compared to wood in term of its strength, durability and textures. This is due to the existence of vascular bundles and parenchyma in the OPT. Therefore this study has attempted to continue the effort by producing laminated veneer lumber (LVL) from OPT and define it as laminated oil palm veneer lumber (LOPVL). The main part of the study was the segregation of oil palm veneer according to stem parts: (i) bottom or top section and (ii) peripheral or core region. In the experiment, four types of mechanical tests were being conducted: (i) edgewise horizontal shear, (ii) flatwise horizontal shear, (iii) edgewise bending and (iv) flatwise bending while for adhesion test, three type of water soak test have been conducted: (i) cold, (ii) hot and (iii) boiling. The test parameters were (i) laminations (BPVTCV, TPVBCV, BCV and TCV) and (ii) adhesives (UF, MUF and PF). Based on the delamination test conducted (cold/ boiling water: 24 hours soaking time, hot water: 2 hours soaking time), it was discovered that all samples showed good bonding result using UF, MUF and PF adhesives. All samples passed the delamination test with 0% delamination ratio. From the mechanical test results, it can be concluded that the strength performance of the LOPVL is justified. The application of different lamination and adhesive significantly affect the overall performance of the LOPVL. As the result, lamination BPVTCV has demonstrated the highest performance compared to lamination TPVBCV, BCV and TCV on UF adhesive (HSSed: 4.58MPa HSSfd: 3.84MPa, MORed: 38.2MPa MORfd: 41.0MPa, MOEed: 6111.2MPa MOEfd: 5625.9MPa) and PF adhesive (HSSed: 4.42MPa HSSfd: 3.66MPa, MORed: 31.9MPa MORfd: 37.9MPa, MOEed: 5482.7MPa MOEfd: 5337.2MPa). Based on this result, it was therefore recommended that the best lamination for making the LOPVL is BPVTCV. Further, the LOPVL could be bonded using either UF or MUF for interior application purposes or PF for exterior application purposes.